THE IMPORTANCE OF INTERNATIONAL RELATIONS IN ENSURING GLOBAL SECURITY IN NEW UZBEKISTAN - Davlatova Saodat Tilovberdievna (Bright Mind Publishing, 2025)
In the era of globalization, international relations play a crucial role in strengthening global security and fostering sustainable development. For New Uzbekistan, building effective diplomatic ties, expanding regional cooperation, and participating actively in international organizations are essential steps toward ensuring peace and stability. Strengthening foreign policy based on mutual respect, sovereignty, and constructive dialogue helps to prevent conflicts, enhance economic integration, and address global challenges such as terrorism, climate change, and cyber threats. The importance of international relations in New Uzbekistan lies not only in promoting national interests but also in contributing to collective security, stability, and prosperity on a global scale.
Keywords: International Relations, Global Security, New Uzbekistan, Diplomacy, Regional Cooperation, Peace, Sustainable Development.